Chlamydia trachomatis genotypes in sexually transmitted disease clinic attendees in Colombo, Sri Lanka - H. Attanayaka; C. L. Goonasekara; N. Abeygunasekera; J. Elvitigala; K. Gunasekera (Sri Lankan Journal of Infectious Diseases, 2023)
Introduction: Chlamydia trachomatis (CT) is the most common cause of non-gonococcal urethritis. Prevalence of CT infections in Sri Lanka was 17.1% in females in 2015. Real-time PCR for diagnostic testing of CT was started in 2015 but screening programmes have not been initiated due to the high cost. The aim of this study was to determine the genotypes of CT in patients from Colombo, since genotypic distribution in Sri Lanka is not known. Methods: Stored first void urine samples (n=208) from a previous study on patients attending two clinics in Colombo were used. Samples that were positive by Artus C. trachomatis Plus RG Real time PCR (Qiagen) were retested with a nested PCR described previously, which generated 15 ompA sequences suitable for standard sequencing. Results: Genovars E (n=6; 40%), F (n=5; 33.3%), G (n=3; 20%) and H (n=1; 6.7%) were identified. Conclusions: As seen in most parts of the world, genovar E and F were the most commonly detected CT genovars among patients in Colombo.